Pengikatan Jaminan Kebendaan dalam Kontrak Pembiayaan MudÌ£aÌ„rabah sebagai Upaya Penyelesaian Sengketa Debitur Wanprestasi (Analisis Putusan Mahkamah Agung Nomor 272/K/AG/2015 tentang Pembiayaan Mudharabah) - Harahap, Mhd. Yadi (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The imposition of collateral in mudÌ£aÌ„rabah financing contracts is a separate issue for Islamic banks even though in principle Islamic banks are not required to ask for collateral, but in practice, collateral is one of the elements that must be met by business actors in mudÌ£aÌ„rabah financing contracts. When the collateral is not applied, problems often arise in the case of debtor default. The problem in this study is whether the imposition of collateral can be used as an effort to resolve debtor disputes in mudÌ£aÌ„rabah financing contracts. To answer the research question, the method used is a normative juridical research method where the law is not only seen as law in books but also the law in action with the statutory approach and case study approach, namely the decision of the Mahkamah Agung. The results of the study presented that binding guarantees in mudÌ£aÌ„rabah financing contracts can be used as anticipation to minimize the risk of loss based on article 39 of Law no. 21 of 2008 concerning Islamic Banking. When the business actor defaults, neglects, and breaches the contract in mudÌ£aÌ„rabah financing, the guarantee can be used as an effort to mitigate the settlement of mudÌ£aÌ„rabah financing disputes to pay off obligations to Islamic banks.